The Survival time of Terminal Cancer Patients: Prediction Based on Clinical Parameters and Simple Prognostic Scores. Issue 1 (March 2014) - Kim, A Sol; Youn, Chang Ho; Ko, Hae Jin; Kim, Hyo Min
Aim: By examining clinical parameters associated with survival time and analyzing patients' survival times using prognostic scores, this study aimed to provide helpful information related to the treatment of terminal cancer patients. Methods: We retrospectively reviewed the medical records of 415 inpatients who died in the hospices of two hospitals from March 2009 to August 2011 then analyzed differences in survival times and relative risk for clinical parameters and prognostic scores. Results: There were 15 parameters associated with survival time. Performance decline was the most influential factor. The optimal scores for predicting four-week survival were over 4.5 on the Palliative Prognostic Index (PPI), over 10 on the Palliative Prognostic (PaP) Score, and 30 or under on the Palliative Performance Scale (PPS). Conclusion: Performance decline is a major factor affecting survival time. The PaP is the most useful tool for predicting four-week survival, with an optimal value of over 10.